Explaining differing perceptions of employees' skill needs: the case of garment workers in Ethiopia. (8th January 2018) - Yamada, Shoko; Otchia, Christian S.; Taniguchi, Kyoko
Abstract: The Ethiopian economy has grown significantly and the government has prioritized industrial skills development and expanded technical and vocational education and training (TVET). However, mismatches between the skills available and the skills required are widespread and the unemployment rate for TVET graduates is high. Little scholarly effort has been made to empirically identify the exact types and domains of skills in which these supply–demand mismatches happen. The present study relies on interviews with 30 vocational trainers, 19 employees, 13 factory managers and 3 garment industry experts. To measure the perception gaps between the supply and demand sides of worker skills and explain why mismatches occur, we conducted an assessment in which assessors from among the factory managers and vocational trainers along with the three industry experts concurrently graded the garment‐manufacturing vocational skills of the same workers. For this purpose, we developed a unique instrument that captures the knowledge and skills of workers in real work environments. The analysis reveals that TVET trainers expect students to have comprehensive skills and grade the skills of workers more generously, whereas factory managers expect not variety but quality, and score workers' performance more critically. Differences in the educational backgrounds and practical experience of assessors contribute to these gaps. The evidence from this study suggests that the vocational skills assessment instrument we have developed for our research is valid and can serve as a basis for future large‐scale performance assessments.